2017
DOI: 10.9790/2380-1002018386
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Therapeutic Management of Feline Mycoplasmosis

Abstract: Mycoplasma haemofelis and Candidatus Mycoplasma haemominutum (formerly known as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Seven cats (6.3%) were infected with Candidatus M. haemominutum, two (1.2%) with M. haemofelis , and one (0.9%) with Candidatus M. turicensis. A previous study conducted in Thrissur, Kerala ( 16 ) detected a prevalence of 23% of Candidatus M. haemominutum and 1% of M. haemofelis by PCR. Candidatus M. haematoparvum-like organisms (0.7%) reported previously from the USA ( 41 ) were not detected in the present study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Seven cats (6.3%) were infected with Candidatus M. haemominutum, two (1.2%) with M. haemofelis , and one (0.9%) with Candidatus M. turicensis. A previous study conducted in Thrissur, Kerala ( 16 ) detected a prevalence of 23% of Candidatus M. haemominutum and 1% of M. haemofelis by PCR. Candidatus M. haematoparvum-like organisms (0.7%) reported previously from the USA ( 41 ) were not detected in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…There were only a few documented reports on the molecular detection of these infectious agents in cats from India ( 15 , 16 ). Hence, the present communication focuses on the generation of baseline information regarding the presence and distribution of hemoparasites and hemoplasmas in cats of southern India.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the cat was treated with long-acting oxytetracycline at a dose of 20 mg/kg BW intramuscularly and repeated every 3 days for 2 weeks. Ameldev and Tresamol (2017) reported that Oxytetracycline hydrochloride at a dose of 25 mg/kg BW intramuscularly repeated 3 days for 7 days and subcutaneously for 2 weeks is effective as a therapy for haemoplasmosis infection. Administration of Doxycycline (dose of 10 mg/kg BW orally) is generally preferred as long-term therapy for up to 8 weeks in cats suffering from haemoplasmosis.…”
Section: Resultsmentioning
confidence: 99%